Soybean Lectin Enhances Biofilm Formation by Bradyrhizobium japonicum in the Absence of Plants - Pérez-Giménez, Julieta; Mongiardini, Elías J.; Althabegoiti, M. Julia; Covelli, Julieta; Quelas, J. Ignacio; López-García, Silvina L.; Lodeiro, Aníbal R. (International Journal of Microbiology, 2009)
Soybean lectin (SBL) purified from soybean seeds by affinity chromatography strongly bound to Bradyrhizobium japonicum USDA 110 cell surface. This lectin enhanced biofilm formation by B. japonicum in a concentration-dependent manner. Presence of galactose during biofilm formation had different effects in the presence or absence of SBL. Biofilms were completely inhibited in the presence of both SBL and galactose, while in the absence of SBL, galactose was less inhibitory. SBL was very stable, since its agglutinating activity of B. japonicum cells as well as of human group A+ erythrocytes was resistant to preincubation for one week at 60°C. Hence, we propose that plant remnants might constitute a source of this lectin, which might remain active in soil and thus favor B. japonicum biofilm formation in the interval between soybean crop seasons.